Nonsteroidal Anti-inflammatory Drugs and Clinical Outcomes among Men with Prostate Cancer: A Systematic Review and Meta-analysis - Thakker, Divyesh; Raval, Amit D; Raval, Nilixa; Vyas, Ami (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) have shown properties of inhibiting the progression of prostate cancer (PCa) in preclinical studies. However, epidemiological studies yield mixed results on the effectiveness of NSAIDs in PCa. Objective: The objective of this study was to determine the effect of NSAID use on clinical outcomes in PCa using systematic review and meta-analysis. Methods: Original articles published until the 1st week of October, 2016, were searched in electronic databases (Medline-Ovid, PubMed, Scopus, The Cochrane Library, and Web of Science) for studies on NSAID use in PCa. The main clinical outcomes for the review were: PCa-specific (PCM) and all-cause mortality (ACM), biochemical recurrence (BCR), and metastases. Meta-analysis was performed to calculate the pooled hazard ratio (pHR) and their 95% confidence interval (95% CI). Heterogeneity between the studies was examined using I2 statistics. Appropriate subgroup analyses were conducted to explore the reasons for heterogeneity. Results: Out of 4216 retrieved citations, 24 observational studies and two randomized controlled studies with a total of 89,436 men with PCa met the inclusion criteria. Overall, any NSAID use was not associated with PCM, ACM, and BCR, with significant heterogeneity. Neither precancer treatment aspirin use (pHR: 1.00, 95% CI: 0.83, 1.19, P = 0.97, 5 studies, I2: 51%) nor postcancer treatment aspirin use (pHR: 0.94, 95% CI: 0.72, 1.23, P = 0.67, 8 studies, I2: 86%) was associated with PCM. Similar findings, that is, no significant association was observed for NSAID use and ACM or BCR overall, and in subgroup by types of NSAID use, and NSAID use following radiation or surgery. Conclusion: Although NSAID use was not associated with ACM, PCM, or BCR among men with PCa, significant heterogeneity remained in the included studies even after subgroup analyses.
Keywords: Aspirin; biochemical recurrence; prostate cancer; prostate cancer-specific mortality